Improvement of Methodical Maintenance of Professional Training of Masters in Direction “Land Management and Cadastres” in Field of Land Resources Management - T. A. Boronenko; V. S. Fedotova (Научный диалог, 2018)
Relevance of the work is caused by the need of professional training of masters of land management and cadastres for activity in management of land resources and real estate objects. The attention is focused on the obligation to comply with the requirements of the Federal state educational standard for the implementation of the content of educational programmes of master’s training in the electronic information and educational environment, including programmes with the use of distance learning technologies. The didactic possibilities of electronic educational resources of distance learning systems as modern multimedia and interactive means of teaching master students are characterized. The conclusion is made about possibility of improvement of methodical training of masters in “Land management and cadastres” in the field of land administration through the establishment and implementation into the pedagogical practice of an electronic educational resource of the same name. The main requirements imposed to electronic educational resources are marked: availability of methodical recommendations and thematic planning of a course; use of multimedia and interactive format of representation of electronic content of a training course; convenience of navigation on a resource; the organized feedback with the teacher; open system of estimation and control of educational activity of the trained. The results of the creation of an electronic educational resource for masters of the direction “Land management and cadastres” on the course “Management of land resources and real estate” are demonstrated. The conclusion about the prevailing positive characteristics of e-learning resources is made. The question of the need for special training and motivation of teachers to create electronic educational resources and their placing on the platform of distance learning is raised.